FOLKLORE SITE OF KARUMAN AS SOURCE OF STUDY OF HISTORY IN TLOGOMAS MALANG - Diah Ayu Wulan (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
Folklore is a testimony passed down from generation to generation which can be in the form of a folklore. Folklore that develops in the Tlogomas community is in the form of the story of Bango Samparan and his companions the form of the legacy is the Karuman Site. This study aims to answer the origins of suggestion folklore site of Karuman, describes folklore site Karuman can become source history of Tlogomas, and to describe the social value of the Karuman Site in the Tlogomas community. Type of research used in this research is descriptive qualitative. Data collection technique used is interview. Source of the data used in this study is the result of interviews with stakeholders of the Karuman Site and some responses from the local community. Results research shows that around the area of the Karuman Site was formerly a princess area and flower gardens. Site of Karuman in the form of punden is Mbah Karuman's meal which was indicated as Bango Sampan, stepfather of Ken Arok. Folklore gets number of response from public around which form response of positive or negative.